Evaluasi Penurunan Skala Nyeri pada Pasien Pasca Seksio Caesarea dengan Injeksi Ketorolac dengan NRS dan FPS : Evaluasi Penurunan Skala Nyeri pada Pasien Pasca Seksio Caesarea dengan Injeksi Ketorolac dengan NRS dan FPS - Annis Rahmawaty; Gunawan Firmansyah; Rifda Naufa Lina (JURNAL FARMASI DAN MAKANAN, 2025)
Caesarean section (SC) is a surgical procedure to address complications during childbirth, a complication that is often experienced by post-SC patients is pain. Adequate pain management is important to ensure optimal recovery of post-SC patients. This study aimed to evaluate the decrease in the pain scale of post-SC patients after the use of Ketorolac injection. This study uses an observational study design with a retrospective analytical approach. The study sample is the medical records of post-SC patients who received Ketorolac injection as an analgesia in the February-April 2023 period. The sampling technique used accidental sampling according to the criteria totaling 89 people. The data collected included the demographic characteristics of the patient, the pain scale using NRS, FPS before and after the use of Ketorolac injection. The results of the study showed the age characteristics of pregnant women who had the most SC at the age of 26-30 years. The use of Ketorolac injection lowered the pain scale of post-SC patients with moderate and mild pain levels as evidenced by 85.3% of respondents experiencing a decrease in pain. Pain reduction after ketorolac injection averaged 1-2 pain scales with a duration of 2-4 hours after administration. The NRS,FPS pain assessment method can be used effectively in measuring the decrease in the pain scale of post-SC patients. Adequate post-SC pain management using Ketorolac injection can be an option to improve the quality of care for post-SC patients